2020
DOI: 10.3390/polym12112731
|View full text |Cite
|
Sign up to set email alerts
|

3D Nanoarchitecture of Polyaniline-MoS2 Hybrid Material for Hg(II) Adsorption Properties

Abstract: We report the facile hydrothermal synthesis of polyaniline (PANI)-modified molybdenum disulfide (MoS2) nanosheets to fabricate a novel organic–inorganic hybrid material. The prepared 3D nanomaterial was characterized by field emission scanning electron microscopy, high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffraction studies. The results indicate the successful synthesis of PANI–MoS2 hybrid material. The PANI–MoS2 was used to study the extraction and preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The work by Alsame et al [ 9 ] is focused on an ease hydrothermal synthesis of polyaniline (PANI)-modified molybdenum disulfide (MoS2) nanosheets employed to obtain a novel 3D organic–inorganic hybrid material. An exhaustive characterization of the obtained material by using field emission scanning electron microscopy, high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffraction studies led the authors to conclude that the obtaining procedure of the organic–inorganic hybrid material (PANI–MoS 2 ) was successful.…”
mentioning
confidence: 99%
“…The work by Alsame et al [ 9 ] is focused on an ease hydrothermal synthesis of polyaniline (PANI)-modified molybdenum disulfide (MoS2) nanosheets employed to obtain a novel 3D organic–inorganic hybrid material. An exhaustive characterization of the obtained material by using field emission scanning electron microscopy, high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffraction studies led the authors to conclude that the obtaining procedure of the organic–inorganic hybrid material (PANI–MoS 2 ) was successful.…”
mentioning
confidence: 99%
“…However, the inherent limitations of an injection molding tool fabricated with Al-filled epoxy resin include their low mechanical properties and heat transfer capability compared with STAVAX stainless steel [41]. These limitations can further be improved by adding copper powders [42,43], molybdenum disulfide [44][45][46][47], zirconia ceramics [48,49], or silicon nitride ceramics [50][51][52][53] particles in the mixture. These issues are currently being investigated, and the results will be presented in a later study.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, metal hydroxides are excellent candidates for drug delivery in view of their porous structure with large surface active sites, as well as complete degradation in acidic environments. 318,319 For example, Liao et al developed H-MnFe(OH)x nanocapsules with hollow structures of about 90 nm in size by selecting silica NPs as hard templates for the in situ growth of MnFe(OH)x, which could accommodate a variety of therapeutic drugs. 320 In vivo experiments showed that Mn 2+ /Fe 3+ released from nanocapsule could effectively catalyze the breakdown of H 2 O 2 to O 2 in the tumor microenvironment, thus significantly improving the efficacy of PDT/chemotherapy synergistic treatment.…”
Section: Light-responsive Npsmentioning
confidence: 99%